Superação da dormência e o uso de Fungicida em diásporos de teca - Coimbra, Elza C.; Vazquez, Gisele H. [UNESP]; Nogueira, Thaissa O. (FapUNIFESP (SciELO), 2014)
The objective of this research was to test methods of breaking dormancy, besides to assess the efficiency of fungicide in storage of teak diaspores which suffered pre-germination treatments. The experimental design was in completely randomized factorial scheme 7 × 2 × 2 (seven methods of dormancy breaking, with and without fungicide; two stages of evaluation , zero and after 120 days). The methods employed were: immersion in running water (24 h) and in hot water (85-90 °C for 8 min); scarification with sandpaper + immersion in standing water (48 h); scarification with sulfuric acid for 15 min + running water washing (72 h); heating in oven at 80 °C (4 h for 3 days) + standing water immersion (12 h); solarization for 48 hours + standing water immersion (12 h); and the control. The methods of dormancy breaking with dry heating of the teak fruits were able to shorten, increase, and standardize the germination, being the use of the solar collector a good choice for not consuming energy and of low cost. The use of Fludioxonil + Metalaxyl-M fungicide and the storage of teak diaspores which have suffered dormancy breaking treatment are not recommended.
Breaking of dormancy and the fungicide use in teak fruits
Keywords: Scarification; Solar collector; Tectona grandis